The tourist-religious mobility of the “silver-haired people”. The case of Pietrelcina (BN) - La Rocca, Rosa Anna; Fistola, Romano (TeMA - Journal of Land Use, Mobility and Environment, 2018)
This study deals with religious tourism as a particular social and cultural activity attaining high levels of interest also in the scienti c context. Within this form of tourism, the segment of “senior travelers” plays an important role considering the increase of the popula- tion aging phenomenon. Although there is not yet a unique and shared de nition of senior tourism, it is possible to outline some char- acteristics to de ne this speci c form of use of the urban system. The case study of Pietrelcina (BN) in Campania has been considered as a meaningful example of international religious pole connected to San Pio cult. In this regard, the study is aimed to explore the possibilities of de ning territorial strategies for the promotion of territorial resources. The main objective of this study is to overcome the sectorial approach, based on the “mono-pole supply” (the organization of tourist ows “exclusively oriented”, centralized in the most popular destination), suggesting a systemic-territorial supply recon guration aimed at improving the accessibility to older slow tourism. The study, thus, proposes a recon guration of the territorial organization in order to pre gure a systemic territorial-supply aimed at improving particularly accessibility referred to older slow tourism. Slow tourism as innovative form of territorial use could improve the relationship between tourism and territory that was the original sense of pilgrimage.